2012
DOI: 10.1007/s11033-012-1482-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection and coronary heart disease risk: a meta-analysis

Abstract: The chronic inflammatory process including cytomegalovirus (CMV) infection has been hypothesized to induce the progression of atherosclerosis in coronary heart disease (CHD). Numbers studies were conducted to analyze the association between CMV infection and risk of CHD, but no clear consensus had been reached. To assess this relationship more precisely, a meta-analysis was performed. The electronic databases PubMed, Embase, and CNKI were searched; data were extracted and analyzed independently by two investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…In a populationbased study involving 1468 participants, a composite measure of TNF-α and IL-6 mediated a substantial proportion of the association between CMV and allcause (18.9%, P < 0.001) and cardiovascular (29.0%, P = 0.02) mortality (Roberts et al 2010). A metaanalysis based on 9000 CMV-infected individuals and 8.608 controls from six prospective studies and 49 retrospective case-control studies showed that CMV infection overall has an odds ratio of 1.67 for CAD risk (Ji et al 2012). The European Prospective Investigation into Cancer (EPIC) study identified an association between higher levels of CMV-IgG and ischemic heart disease (with a hazard ratio of 1.4 when compared to seronegativity).…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 99%
“…In a populationbased study involving 1468 participants, a composite measure of TNF-α and IL-6 mediated a substantial proportion of the association between CMV and allcause (18.9%, P < 0.001) and cardiovascular (29.0%, P = 0.02) mortality (Roberts et al 2010). A metaanalysis based on 9000 CMV-infected individuals and 8.608 controls from six prospective studies and 49 retrospective case-control studies showed that CMV infection overall has an odds ratio of 1.67 for CAD risk (Ji et al 2012). The European Prospective Investigation into Cancer (EPIC) study identified an association between higher levels of CMV-IgG and ischemic heart disease (with a hazard ratio of 1.4 when compared to seronegativity).…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 99%
“…However, a sizeable minority of patients suffering from atherosclerosis do not harbour the classical risk factors. Other predisposing factors appear to contribute to the disease process including chronic viral infections (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…A similar matter of recent debate is if and how infection with human cytomegalovirus (HCMV), another human herpes virus, could be linked with certain autoimmune diseases and how both conditions could interfere with each other. Several features including its extensive manipulation of adaptive and innate immune functions [25], the very large coding capacity [6], its lytic replication in multiple tissues [7] both locally and systemically, its lifelong persistence during subsequent phases of latency and reactivation, and its ubiquitous prevalence in human populations readily explain why HCMV was frequently linked with AID but also with further acquired disorders like arteriosclerosis and vascular disease [8], immune aging [9], and certain types of tumors [10]. …”
Section: Introductionmentioning
confidence: 99%